2022
DOI: 10.1186/s12884-022-04410-x
|View full text |Cite
|
Sign up to set email alerts
|

What are the strategies for implementing primary care models in maternity? A systematic review on midwifery units

Abstract: Background Midwifery Units (MUs) are associated with optimal perinatal outcomes, improved service users’ and professionals’ satisfaction as well as being the most cost-effective option. However, they still do not represent the mainstream option of maternity care in many countries. Understanding effective strategies to integrate this model of care into maternity services could support and inform the MU implementation process that many countries and regions still need to approach. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…They can vary in the type of sexual and reproductive health services they provide (e.g., preconception, ante, intra and postpartum or only intrapartum), location (freestanding or alongside a hospital with obstetric services) or their level of integration with the healthcare system (public, integrated or private). Despite the evidence, they are still not well established in many countries (Rayment et al, 2020); therefore, research is now focusing on influences and strategies to support the spread and scaling up of this model of care internationally (Batinelli et al, 2022;Rocca-Ihenacho et al, 2022;Tracy et al, 2005;Walsh et al, 2020). A systematic review of influences on implementation, which included studies from China, US, England, Canada, Brazil and Iran, identified that this type of complex innovation requires a multi-layered approach that address cultural, organisational and professional elements (Batinelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can vary in the type of sexual and reproductive health services they provide (e.g., preconception, ante, intra and postpartum or only intrapartum), location (freestanding or alongside a hospital with obstetric services) or their level of integration with the healthcare system (public, integrated or private). Despite the evidence, they are still not well established in many countries (Rayment et al, 2020); therefore, research is now focusing on influences and strategies to support the spread and scaling up of this model of care internationally (Batinelli et al, 2022;Rocca-Ihenacho et al, 2022;Tracy et al, 2005;Walsh et al, 2020). A systematic review of influences on implementation, which included studies from China, US, England, Canada, Brazil and Iran, identified that this type of complex innovation requires a multi-layered approach that address cultural, organisational and professional elements (Batinelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the evidence, they are still not well established in many countries (Rayment et al, 2020); therefore, research is now focusing on influences and strategies to support the spread and scaling up of this model of care internationally (Batinelli et al, 2022;Rocca-Ihenacho et al, 2022;Tracy et al, 2005;Walsh et al, 2020). A systematic review of influences on implementation, which included studies from China, US, England, Canada, Brazil and Iran, identified that this type of complex innovation requires a multi-layered approach that address cultural, organisational and professional elements (Batinelli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Our study findings also align with similar studies in HICs [ 27 30 ] and the frameworks and standards that have been developed based on those studies [ 31 – 33 ]. For example, the following factors have been identified as important in a range of settings as well as in this study: an enabling policy environment including adequate financial and human resourcing, [ 28 33 ] mainstreaming MLBCs as a core element of the service rather than as an ‘optional extra’, [ 27 , 28 , 30 ] strong and inspirational midwifery leadership, [ 27 , 28 , 30 ] education and training programmes that prepare midwives with the competence and confidence to support physiological birth and make decisions independently, [ 28 , 30 ] interdisciplinary and interfacility collaboration built on relationships of trust and respect [ 28 , 30 ]. Supportive leadership helps create a positive work environment for midwives, encouraging their professional development and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Within maternal-newborn care, there are increasing examples of implementation science applications, focusing on topics such as prioritizing content areas for implementation research [ 11 ] and practice [ 12 ], identifying and examining the effectiveness of different implementation strategies [ 13 15 ], and exploring barriers and facilitators to implementation [ 15 17 ]. While this literature makes an essential contribution to advancing our understanding of evidence-informed strategies to implement evidence and the potential challenges, it typically has not focused on the entire implementation process needed to bring about change (i.e., taking a planned action [ 18 ] approach to changes).…”
Section: Introductionmentioning
confidence: 99%